Manganese effects on in vitro development of lesser centaury [Centaurium pulchellum (Sw.) Druce] - Todorović Slađana; Giba Z.; Simonović Ana; Božić Dragana; Banjanac Tijana; Grubišić D. (Archives of Biological Sciences, 2009)
To determine the manganese requirement necessary for optimal development of lesser centaury [Centaurium pulchellum (Sw.) Druce] in vitro, we investigated the effect of exogenously applied Mn on different developmental processes such as growth, flowering, fruiting, and seed germination. The application of Mn had no effect on stem length, except at the highest concentration of 10-2 M, which was inhibitory. In addition, C. pulchellum plants were capable of in vitro flowering and fruiting even on media without added Mn. However, Mn content in the media affected seed dimensions, since both length and width of the seeds increased with increasing Mn concentration. Moreover, both excess and absence of Mn in the media caused appearance of necrotic plants. Exogenously applied Mn had no effect on seed germination percentage, except at concentrations greater than 3x10-3 M.